The relationship between degradation of myofibrillar structural proteins and texture of superchilled grass carp (Ctenopharyngodon idella) fillet. (15th December 2019) - Yang, Fang; Jia, Shengnan; Liu, Jixuan; Gao, Pei; Yu, Dawei; Jiang, Qixing; Xu, Yanshun; Yu, Peipei; Xia, Wenshui; Zhan, Xiaobei
Highlights: Small myofibrillar structural proteins degradation initiated fish softening. More giant myofibrillar structural proteins degraded during later storage. Desmin and titin contributed more to softening comparatively. Abstract: Softening is always a problem in fish preservation. This study was aimed to investigate the role of myofibrillar structural proteins degradation in fish softening. The changes of myofibrillar structural proteins, muscle ultrastructure, myofibril fragmentation, and shear force were studied. The results indicated that during the superchilled preservation of grass carp ( Ctenopharyngodon idella ), small (low-molecular-weight) myofibrillar structural proteins like desmin and troponin-T initiated textural deterioration, leading to Z-disk weakening and actin loosening. In contrast, giant (high-molecular-weight) myofibrillar structural proteins like titin and nebulin were degraded in more amount in the later storage, contributing to Z-disk and M-band disassembly and vague of light and dark regions (I and A bands). Compared to each other, desmin and titin played more important part in softening. All these changes were involved in the increase of muscle fibril segments and the sharp decrease of shear force.